Pengaruh Fraud Pentagon Theory Dalam Mendeteksi Fraudulent Financial Reporting Dengan F-Score Model - Sitoresmi, Dyah; Fakhruddin, Iwan; Fitriati, Azmi; Setyadi, Edi Joko (Politeknik Ganesha Medan, 2024)
In an era of intense competition in the business world, companies may often be under pressure to demonstrate superior financial performance, even if it does not accurately reflect their true position. Maintaining reputation in the eyes of external stakeholders is the main motivation. In this context, information in performance reports is often manipulated. This study aims to detect fraudulent financial reporting using the fraud pentagon theory as well as the f-score model. The research population involves food and beverage subsector companies listed on the Indonesia Stock Exchange during the 2017-2021 period. A sample of 21 companies was obtained using purposive sampling technique, so that the unit of analysis amounted to 105. Stata was used as the analysis software. The results showed that financial target, effective monitoring, and change of directors had no effect on fraudulent financial reporting. However, the quality of external auditor has a negative effect. While the frequency of CEO’s picture has a positive effect fraudulent financial reporting.